PENINGKATAN HASIL BELAJAR IPA MELALUI MODEL LSQ PADA POKOK BAHASAN PENGUKURAN DI SMP N 2 SAYUNG - Endang Puji Astuti (Universitas PGRI Semarang, 2014)
Background of the problem in this research is the lack of student understanding of the material and the lack of involvement of the student in the learning so that student learning outcomes in physics low. Therefore, it needs to be an application of learning models by using Learning Stars with a Question as an alternative to be applied.The purpose of the research is to know about the improvement of learning result IPA using the model of Learning Stars with a Question on the subject of measurement in SMP 2 Sayung. This research is Classroom Action Research (CAR). The subjects of this research were students of class VII F SMP N 2 Sayung academic year 2013/2014, amounting to 22 learners.This is supported by the teachers performance during learning. Based on observations of teacher performance, quality of teacher performance increased from 66.25% to 71.75% and increased to 86.36%. This research consisted of three cycles, and each cycle consists of four phases: planning, implementation, observation and reflection. Based on the test results of students cycle I, cycle II and cycle III showed increasing in cognitive ability class VII F from 54,5% to 77,27% and increased to 86,36%. It can be concluded that the learning model LSQ (Learning Stars with a Question) can improve student learning outcomes on the subject of class VII F Measurement of SMP N 2 Sayung academic year 2013/2014. Model pembelajaran kooperatif merupakan pembelajaran yang dilakukan secara berkelompok, yang mana membantu siswa dalam mengembangkan pemahaman dan sikapnya sesuai dengan kehidupan nyata sehingga dalam